Bridging Educational Leadership, Curriculum Theory and Didaktik: Non-affirmative Theory of Education - Uljens, Michael; Ylimaki, Rose M. (Educational Governance Research, 2017)
curriculum; educational leadership; philosophy of education; Bildung